Natural strategies to optimize estrogen levels in aging women: mini review - Bolgova, Olena; Shypilova, Inna; Mavrych, Volodymyr (Frontiers in Aging, 2025)
IntroductionMenopause triggers declining estradiol, causing vasomotor symptoms, bone loss, and urogenital changes. Despite hormone therapy’s effectiveness, safety concerns drive 40%–50% of Western women toward natural alternatives.AimTo evaluate evidence supporting non-pharmacological interventions that modulate endogenous estrogen activity in postmenopausal women.Methods48 high-quality publications (2015–2025) examining dietary interventions, micronutrient supplementation, gut microbiome modulation, lifestyle modifications, and botanical remedies for menopausal symptoms were analyzed and included in this review. Selection criteria included randomized controlled trials, systematic reviews, meta-analyses, and cohort studies specifically addressing natural interventions in perimenopausal and postmenopausal women.ResultsMultiple natural approaches demonstrated clinically meaningful effects. Dietary phytoestrogens (50–80 mg/day isoflavones) reduced severe hot flashes by up to 92%, improved metabolic parameters, and were confirmed safe for reproductive tissues. Flaxseed lignans reduced perimenopausal symptoms. Combined vitamin E and omega-3 lowered hot flush intensity, while vitamin E alone showed estrogenic receptor activation. Curcumin (500 mg/day) reduced hot flashes after 4 weeks and improved metabolic profiles. Probiotics containing L. brevis KABP052 increased circulating estrogens by up to 26% over 12 weeks. Stress reduction interventions improved quality of life, and cognitive behavioral therapy reduced insomnia severity. Botanicals including black cohosh, red clover, and rhapontic rhubarb reduced vasomotor symptoms, while resveratrol (75 mg twice daily) significantly improved bone mineral density over 12 months. Research gaps remain regarding dosing and genetic variability.ConclusionA multi-domain approach incorporating phytoestrogen-rich foods, targeted micronutrients, gut microbiome optimization, and regular exercise provides evidence-based options for managing estrogen decline. While these approaches cannot fully replace hormone therapy, they provide valuable alternatives for women with contraindications or preferences against pharmaceutical intervention. Future research should focus on personalized approaches incorporating genetic profiling.